The Modern Records Management Program: An Overview of Electronic Records Management Standards. - Seymour, Jennifer (Bulletin of the Association for Information Science & Technology)
EDITOR'S SUMMARY Standardization is fundamental for bringing a vast variety of electronic records under control. It enables capturing and preserving original records as well as evidence of any access or change to the records. Creating standards within and across organizations is an extreme challenge that must be met. The 2011 Presidential Memorandum on Managing Government Records and subsequent 2012 Directive established values and strategic direction for managing federal electronic records without creating strict standards. The Battelle Record Management Office relies on a Defense Department standard for enterprise content management systems to be secure, searchable and capable of preserving contextual relationships and on the Code of Federal Regulations regarding equivalence of electronic records and signatures to paper. The result demonstrates a record's integrity and authenticity and enables it to be discovered and accessed. Defined access permissions and an audit trail add further assurances. Interoperability through application program interface layers is another requirement, being addressed through advanced platform development, which may provide the solution for authenticity and contextual preservation.